Efficient fault diagnosis of proton exchange membrane fuel cell using external magnetic field measurement - Zhongyong Liu; Yuning Sun; Lei Mao; Heng Zhang; Lisa Jackson; Qiang Wu; Shouxiang Lu (2022)
Fault diagnosis has been considered as a critical solution for improving the reliability of proton exchange membrane fuel cell (PEMFC) system. This study proposes an efficient PEMFC fault diagnosis technique, where PEMFC external magnetic field is measured during its operation, from which PEMFC performance degradation mechanisms and corresponding faults can be identified. In the analysis, a PEMFC numerical model is constructed to explore the relation between external magnetic field and PEMFC state of health. Furthermore, a non-invasive measurement strategy is proposed to collect external magnetic field during the operation. With the measurements, an efficient PEMFC fault diagnosis method is proposed, and its effectiveness in identifying PEMFC water management issues is investigated using PEMFC test data. Results demonstrate that PEMFC flooding and dehydration can be discriminated with good quality, and the faulty level can also be identified accurately.